Cardiovascular, cognitive, and mental health benefits of running and walking: A literature review - Arfanda, Poppy Elisano; Aprilo, Ians; Mappaompo, M. Adam -; Awaluddin, Awaluddin; Arimbi, Arimbi; Muhammad, Heryanto Nur (Universitas Tanjungpura, 2025)
Background. Cardiovascular disease, cognitive decline, and mental health disorders are becoming increasingly prevalent worldwide, posing serious threats to public health and individual well-being. These conditions often stem from sedentary lifestyles, poor cardiovascular fitness, and lack of consistent physical activity. As such, identifying effective and accessible strategies for prevention and management is crucial. Objectives. This literature review aims to evaluate the impact of running and walking